Pergeseran Paradigma Tafsir Al-Quran: Analisis Terhadap Tafsir Feminis di Indonesia - Robikah, Siti (Analisis: Jurnal Studi Keislaman, 2019)
The interpretation of the qur’an experienced significant development from the classical to the contemporary era. Shift paradigm is a change in the interpretation paradigm used by classical to contemporary commentators. The methods and approaches used by commentators are not stagnant in one understanding but experience real progress. It can be seen from the ijmali method to the hermeneutic method that is often used by contemporary commentators to interpret the verses of the qur’an. By using the literature method and content analysis, this study explains how changes in interpretation from classical to contemporary focus on feminist approaches. Feminist understanding which is increasingly known in the last century wants the position of equality between men and women or can be called by freeing women from understandings that marginalize women's positions.